2020
DOI: 10.1039/d0ta05865c
|View full text |Cite
|
Sign up to set email alerts
|

Covalent doping of Ni and P on 1T-enriched MoS2 bifunctional 2D-nanostructures with active basal planes and expanded interlayers boosts electrocatalytic water splitting

Abstract: Electrocatalytic water-splitting performance of MoS2 nanostructures can be improved by increasing edge density, activating basal planes, expanding interlayer spacing and stabilizing the 1T-phase. In this work, for the first time,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
52
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 35 publications
3
52
1
Order By: Relevance
“…1,5,6 In this scenario, it is of urgent need to fabricate cost-effective, durable, and highly efficient bifunctional electrocatalysts for both the HER and OER that could be operated in the same electrolytic solution with lower overpotential supply to reduce the energy requirements for the process. 7,8 In this regard, constant efforts to synthesize earth-abundant transition metal-based materials, like sulphides, 9,10 selenides, 11–13 phosphides, 14,15 and metal–organic framework (MOF) derivatives, 7,16 with highly competitive bifunctional electrocatalytic activity, have attracted much attention.…”
Section: Introductionmentioning
confidence: 99%
“…1,5,6 In this scenario, it is of urgent need to fabricate cost-effective, durable, and highly efficient bifunctional electrocatalysts for both the HER and OER that could be operated in the same electrolytic solution with lower overpotential supply to reduce the energy requirements for the process. 7,8 In this regard, constant efforts to synthesize earth-abundant transition metal-based materials, like sulphides, 9,10 selenides, 11–13 phosphides, 14,15 and metal–organic framework (MOF) derivatives, 7,16 with highly competitive bifunctional electrocatalytic activity, have attracted much attention.…”
Section: Introductionmentioning
confidence: 99%
“…These materials have been reported to have large electrical conductivity, high catalytic activity, and improved poisoning resistance for several electrochemical reactions 18‐20 . It has been shown in several recent experimental studies that the presence of transition metals such as tungsten, iron, nickel, and cobalt increases the electron density across the metal centers, whereas anions such as boron, nitrogen, and phosphorus highly improve chemical bonding to promote mechanical and thermal stability and catalytic resilience, as well as to activate the basal planes and increase of interlayer spacing 20‐23 . The bonding of transition metals with phosphorous, carbon, nitrogen, and Sulphur not just induces a weak “ligand effect” which allows for an excellent activity for the dissociation of H 2 , then also provides reasonable bonds to trap catalytic intermediates and avoid the inactivation of catalysts 24 .…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] It has been shown in several recent experimental studies that the presence of transition metals such as tungsten, iron, nickel, and cobalt increases the electron density across the metal centers, whereas anions such as boron, nitrogen, and phosphorus highly improve chemical bonding to promote mechanical and thermal stability and catalytic resilience, as well as to activate the basal planes and increase of interlayer spacing. [20][21][22][23] The bonding of transition metals with phosphorous, carbon, nitrogen, and Sulphur not just induces a weak "ligand effect" which allows for an excellent activity for the dissociation of H 2 , then also provides reasonable bonds to trap catalytic intermediates and avoid the inactivation of catalysts. 24 Some other techniques currently used to enhance the catalytic activity such as morphological control, surface modification, heteroatom doping, and heterojunction construction.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] In particular, phosphorus doping was proved to be a valid way to improve the structural stability of electrode materials owing to the existence of covalent P-M bonds, resulting in superior cycling life. [25][26][27] For example, Liu et al synthesized P-doped MnCo 2 S 4 , which exhibited enhanced electric conductivity and cycling stability. 28 Lin et al prepared P-doped NiCo 2 S 4 nanotubes through a phosphatization reaction, and found the rate capability and cycling stability were significantly improved.…”
Section: Introductionmentioning
confidence: 99%